2012
DOI: 10.1177/0885328211423783
|View full text |Cite
|
Sign up to set email alerts
|

Nanofiber scaffold gradients for interfacial tissue engineering

Abstract: We have designed a 2-spinnerette device that can directly electrospin nanofiber scaffolds containing a gradient in composition that can be used to engineer interfacial tissues such as ligament and tendon. Two types of nanofibers are simultaneously electrospun in an overlapping pattern to create a nonwoven mat of nanofibers containing a composition gradient. The approach is an advance over previous methods due to its versatility - gradients can be formed from any materials that can be electrospun. A dye was use… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
41
0

Year Published

2013
2013
2018
2018

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 59 publications
(41 citation statements)
references
References 48 publications
(88 reference statements)
0
41
0
Order By: Relevance
“…[113] A two-spinneret system was developed to fabricate a nanofiber scaffold gradient in another study. [114][115][116] The nanofibers were fabricated from PCL modified with amorphous calcium phosphate nanoparticles (nACP). PCL scaffolds have shown to support osteogenesis and addition of calcium phosphate can further promote deposition of mineralized ECM.…”
Section: Nanoengineered Bone-ligament Interfacementioning
confidence: 99%
See 2 more Smart Citations
“…[113] A two-spinneret system was developed to fabricate a nanofiber scaffold gradient in another study. [114][115][116] The nanofibers were fabricated from PCL modified with amorphous calcium phosphate nanoparticles (nACP). PCL scaffolds have shown to support osteogenesis and addition of calcium phosphate can further promote deposition of mineralized ECM.…”
Section: Nanoengineered Bone-ligament Interfacementioning
confidence: 99%
“…This trend is similar to the noncalcified to calcified transition in the native ligament-bone interfaces. [116] This study, however, did not consider any structural aspects of native tissue and additional experiments to investigate the effect of mechanical loading on ECM production need to be investigated.…”
Section: Nanoengineered Bone-ligament Interfacementioning
confidence: 99%
See 1 more Smart Citation
“…26 In vitro studies indicate that ACP composites can support mouse osteoblastic cell growth and differentiation. [27][28][29] In addition, recent studies have shown that poly(lactic-co-glycolic acid) microspheres coated with zirconium-modified amorphous calcium phosphate (Zr-ACP) promoted preosteoblast cell attachment and supported cell differentiation. 28,30 Although electrospinning provides fine control over nanofiber synthesis, there are some limitations to applications in tissue engineering such as the inability to deposit fibers without an electric field, slow deposition rates, complex synthesis setups, and poor cell penetration within a fibrous network.…”
Section: Introductionmentioning
confidence: 99%
“…Due to special characteristics of nanofibers such as nanometer sized diameter, high surface area to volume ratio and higher alignment of molecular chains [1], [2], nanofibers are expected to be widely used in many applications such as filter medias [3], drug delivery systems [4] and scaffolds [5]. Nanofibers containing magnetic nanoparticles have potential uses as functional nanofibers for many applications such as sensors and materials for drug delivery systems.…”
Section: Introductionmentioning
confidence: 99%